2015
DOI: 10.1890/14-1482.1
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet photodegradation facilitates microbial litter decomposition in a Mediterranean climate

Abstract: Abstract. Rates of litter decomposition in dryland ecosystems are consistently underestimated by decomposition models driven by temperature, moisture, and litter chemistry. The most common explanation for this pattern is that ultraviolet radiation (UV) increases decomposition through photodegradation of the litter lignin fraction. Alternatively, UV could increase decomposition through effects on microbial activity. To assess the mechanisms underlying UV photodegradation in a semiarid climate, we exposed high-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 41 publications
3
89
3
1
Order By: Relevance
“…Losses of volatile carbon compounds, including CO 2 , CO, and methane (CH 4 ), from recently senesced plant material exposed to natural or artificial radiation have been documented (16)(17)(18) and have been linked to photochemical degradation of cellulose (16) and partial or complete degradation of lignin (19)(20)(21). Recent studies have demonstrated stimulation of litter decomposition and respiration with prior exposure to ultraviolet (UV) (22,23) or full solar radiation (24) in dry Mediterranean ecosystems. Nevertheless, the quantitative significance of photodegradation in terrestrial ecosystems that support greater microbial activity than arid-land ecosystems is generally considered to be minimal (25).…”
Section: Uv Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Losses of volatile carbon compounds, including CO 2 , CO, and methane (CH 4 ), from recently senesced plant material exposed to natural or artificial radiation have been documented (16)(17)(18) and have been linked to photochemical degradation of cellulose (16) and partial or complete degradation of lignin (19)(20)(21). Recent studies have demonstrated stimulation of litter decomposition and respiration with prior exposure to ultraviolet (UV) (22,23) or full solar radiation (24) in dry Mediterranean ecosystems. Nevertheless, the quantitative significance of photodegradation in terrestrial ecosystems that support greater microbial activity than arid-land ecosystems is generally considered to be minimal (25).…”
Section: Uv Radiationmentioning
confidence: 99%
“…2 C and D) provides an important element for conceptual and empirical models aimed to understand the role of photodegradation in litter decomposition in different ecosystems. In addition, the contrasting response of woody and herbaceous species to UV exposure may help to resolve the contradictory results reported for UV effects on photodegradation in terrestrial ecosystems (23,27,(31)(32)(33)(34).…”
Section: Exposure To Solar Radiation Strongly Enhances Subsequent Micmentioning
confidence: 99%
“…Traditional approaches have been based on correlating simple litter characteristics with decay rates for predictive purposes (Meentemeyer 1978;Melillo et al 1982;Coq et al 2010). For example, lignin content, the most abundant plant biopolymer after cellulose, is often negatively correlated with decay rate, especially when root and woody plant tissues are included in analysed samples (Taylor et al 1989), but not in the case of litter photodegradation in dryland systems (Austin and Vivanco 2006;Baker and Allison 2015). Consistent negative correlations with litter decay rates have been also reported for lignin to nitrogen (Lignin/N) (Melillo et al 1982) and carbon to nitrogen (C/N) ratios (Taylor et al 1989), with the latter being more predictive of decay rates in case of substrates with limited lignin content, such as understory herbs (Taylor et al 1989).…”
Section: Originalmentioning
confidence: 99%
“…Si bien en el presente trabajo no se analizó el efecto de la fotodegradación de manera explícita, varios trabajos muestran que este proceso puede alcanzar valores entre 33 y 60% de pérdida de peso en zonas semiáridas y destacan su importancia en el proceso de descomposición Baker and Allison 2015;Day et al 2015). Estos autores proponen que la pérdida de carbono a través de la fotodegradación en estos ecosistemas implica que una fracción importante del C fijado en la biomasa de las plantas se pierde directamente a la atmósfera sin pasar antes a formar parte del C del suelo .…”
unclassified